Preventive Health Care for the Elderly - Stults, Barry M. (1984)
Demographic, economic and humanitarian considerations dictate that effective preventive health care be provided to the elderly. A disease-specific approach to geriatric preventive health care will not suffice; measures to enhance or maintain physical, mental and social function must also be emphasized. Unfortunately, the effectiveness of many preventive care procedures has not been adequately investigated in the elderly. Research is urgently needed to determine the efficacy of and appropriate target population for various geriatric preventive health care measures.